2013
DOI: 10.14202/vetworld.2013.754-760
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of non starch polysaccharide enzymes, synbiotics and phytase on performance, nutrient utilization and gut health in broilers fed with sub-optimal energy diets

Abstract: Aim:In view of the ban on antibiotic growth promoters (AGPs), an attempt was made to explore the possibility of harnessing synergistic effect of non starch polysaccharide (NSP) enzymes, synbiotics and phytase on performance, nutrient retention, gut health and histology of broilers fed with corn-soybean meal based low calorie diets. Materials and Methods:A total of 150 a day-old broiler chicks were weighed, wing banded and randomly distributed into five experimental groups, six replicates per group and five bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Nevertheless, only an interaction trend (P=0.069) between the experimental factors that improved the CP AID coefficient was observed. These results are in line with the usage of synbiotic preparation and phytase combination to reduce the FI and FCR of broilers with simultaneous improvement in organic matter and nitrogen retention, as well as energy availability (Narasimha et al, 2013). Moreover, the mixture of prebiotic and phytase improved the BWG and FCR values in contrast to treatments in which the exogenous enzyme was used as a separate factor (Karimian and Rezaeipour, 2020).…”
Section: Discussionsupporting
confidence: 57%
“…Nevertheless, only an interaction trend (P=0.069) between the experimental factors that improved the CP AID coefficient was observed. These results are in line with the usage of synbiotic preparation and phytase combination to reduce the FI and FCR of broilers with simultaneous improvement in organic matter and nitrogen retention, as well as energy availability (Narasimha et al, 2013). Moreover, the mixture of prebiotic and phytase improved the BWG and FCR values in contrast to treatments in which the exogenous enzyme was used as a separate factor (Karimian and Rezaeipour, 2020).…”
Section: Discussionsupporting
confidence: 57%
“…The present findings were higher than the report of Narasimha et al . [ 30 ] who reported dressing yield (%) ranging from 63.67% to 66.67% in Cobb commercial broiler at 42 days of age. The carcass yield (%) in the present study ranged from 73.77% to 76.04% after 42 days of age which was more than the value observed by Abdel-Raheemand Abd-Allah [ 31 ] who reported 64.45 to 70.68% in Avian -48 broilers of 42 days of age.…”
Section: Resultsmentioning
confidence: 99%
“…However, Sohail et al [28] found that PB had no effect on stress-induced injury in the intestinal morphology of 42-day-old chickens, which might be due to the variation of types and amounts of PB used in different studies. Moreover, the improvement of intestinal morphology and integrated intestinal barrier are important for epithelial cell function, which might be the reason for the improved ATTD of nutrients [29].…”
Section: Discussionmentioning
confidence: 99%